Uwagi o szacowaniu parametrów rozkładu dochodów - Jędrzejczak, Alina (Remarks on the estimation of income distribution parameters, 2006)
The parameters of income distribution models are usually estimated by means of the maximum likelihood method. The maximum likelihood estimators are known to have very good asymptotic properties - they are the most effective, among other things. Nevertheless they are not robust to any deviations from the assumed model. Statistical data concerning wage and income distributions by size are usually contaminated because of the method of gathering information. So the methods of robust estimation, which would find compromise between efficiency and robustness, could be very useful. In the paper we present the results of the estimation of wage distributions in Poland by means of the maximum likelihood method and the optimal B-robust method (OBRE). The basis for the calculation was the individual data coming from the Labour Force Survey.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 99-108